Bioengineering cardiac constructs using 3D printing. Issue 2 (April 2017) - Serpooshan, Vahid; Mahmoudi, Morteza; Hu, Daniel A; Hu, James B; Wu, Sean M
To date, 3D bioprinting has found many actual and potential applications in medicine through assembling cells, biomaterials and supporting factors into living tissues. In particular, the combination of bioprinting and tissue engineering has emerged as a new promising strategy to address the growing need for tissues and organs for both transplantation and basic research. This review summarizes the current progress in the design and printing of bioengineered cardiac tissues for various applications. We highlight the specific biological and technical complexities such as the choice of cells and biomaterials, cell viability and function, vasculature design and tissue architecture. Current challenges and future perspectives in the field of cardiovascular tissue printing are also discussed.